Differences Between Self-Perceived Multiple Intelligences of Urban & Rural Schools Students - Shahzada, Gulap; Ghazi, Safdar Rehman; Ali, Riasat; Khan, Umar Ali; Khan, Abdullah (Richtmann Publishing, 2011)
The purpose of this study was to investigate the differences between self-perceived multiple intelligences of urban and ruralschools students. Measurement of central tendency, mean score, SD for the measurement of self-perceived multiple intelligences and onesample–t test was used for mean comparison of urban and rural schools students. Result showed that there is a significant differencebetween self-perceived verbal/linguistic, logical/mathematical, visual/ spatial and intrapersonal intelligence of urban and rural studentsand there is no significant difference between self-perceived, musical, bodily/kinesthetic, interpersonal and naturalistic intelligence of urbanand rural students.